PENYULUHAN STRATEGI PENCEGAHAN PENULARAN Africa Swine Fever (ASF) PADA MASA WABAH ASF DI DUSUN BINILAKA DESA OELTUA KABUPATEN KUPANG - Katarina Leba; Nofriani Ndun; Frits Francis; Maria Taroci Ka'auni; Selviani Dangur; Rochy Akal; Jessica Maubana; Pedro Nope; Novalino H. G. Kallau; Annytha I. R. Detha; Diana Agustiani Wuri; Larry R. W. Toha (Universitas Nusa Cendana, 2021)
Binilaka is one of Oeltua Village’s hamlet in Kupang Regency. Binilaka Hamlet was reported as an area affected by the ASF (Africa Swine Fever) disease outbreak. ASF is a new disease that occurs in the East Nusa Tenggara region and there is an unknown drug or vaccine to treat this disease. The purpose of this counseling is to provide education to the community in Binilaka Hamlet about strategies to prevent ASF transmission during the outbreak so that the public can find out what prevention strategies need to be done in dealing with the ASF disease outbreak. The results of this counseling indicate an increase in public understanding of the dangers and strategies of preventing ASF. These results are reviewed from public feedback with questions and sharing of experiences related to the incidence of ASF in the environment. It is hoped that the Binilaka Hamlet community will be able to implement the ASF disease prevention strategy properly so that it can reduce the mortality rate of pigs.